Simultaneous occurrence of systemic lupus erythematosus and coeliac disease-like features. Issue 766 (August 1989) - Varkel, Y.; Braester, A.; Suprun, H.; Nusem, D.; Horn, Y.
Abstract : Involvement of the gastrointestinal tract in systemic lupus erythematosus is well documented but small intestinal malabsorption is a rare event. We report a 27 year old woman with systemic lupus erythematosus who had malabsorption and coeliac-like changes on intestinal biopsy. This is the eighth reported case of this association the significance of which is discussed.